Proposed new interior design of Lego Education Centre for Sasbadi Sdn. Bhd. at Jalan Maarof, Bangsar Park, 59000, Bangsar, Kuala Lumpur / Majidah Abdul Majid - Abdul Majid, Majidah (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design o f LEGO Education Centre at 123, Jalan Maarof, Bangsar Park, 59000, Bangsa, Kuala Lumpur. This proposed education centre is to attract users, mostly on kids to experience themselves at this education centre, at the same time to promote the differences style or method of education that is truly different from other education centre in Malaysia. The target market for the users of this education centre is kids from 6 to 12 years old. Parents that are concern about their kid’s education are interested in trying this difference method of education. Every space that proposes would match with the customers’ needs and it could give comfort to them while attending the class. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in LEGO Education Centre. Connected to that, the chosen design style for LEGO Education Centre is based on Modern and fun design, goes all the way with the client’s needs as they want the education centre to have the fun look and at the same time would attract the customers with different image that they would only get in LEGO Education Centre. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and informations about other education centre that use the same system in management, as the proposed education centre. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.